Across the Spectrum from Borderline Dysplasia to Global Pincer Femoroacetabular Impingement: Arthroscopic Outcomes from a Large Hip Arthroscopy Study Group. Issue 7 (31st July 2020) - Kivlan, Benjamin; Nho, Shane; Wolff, Andrew; Salvo, John; Christoforetti, John; Ellis, Thomas; Carreira, Dominic; Matsuda, Dean
Objectives: Outcomes from hip arthroscopy for dysplasia and global pincer FAI have fallen short of those for patients with normal acetabular coverage, but no study has investigated arthroscopic outcomes across the spectrum of acetabular coverage. Our objective is to report comparative hip arthroscopic outcomes of patients with low (borderline dysplasia), normal, and high (global pincer FAI) lateral acetabular coverage. Methods: A retrospective analysis of prospectively-collected data from a large multi-center registry (seven United States centers) was performed. Primary hip arthroscopy patients were assigned to one of three groups based on preoperative lateral center-edge angle (LCEA): borderline dysplasia (≤25°), normal (26-38°), and pincer FAI (≥39°). Repeated measures ANOVA compared pre-operative to 2-year minimum post-operative iHOT-12 scores. Subsequent ANOVA determined the effect of acetabular coverage on magnitude of change in scores. Results: Of 437 patients, the only statistical difference between groups was lower prevalence of acetabuloplasty in the borderline dysplasia group (p=0.001). A significant improvement in the pre-operative to post-operative iHOT-12 scores for patients with normal acetabular coverage, acetabular undercoverage, and acetabular overcoverage was observed; F(1, 339)=311.06; p<0.001, with no statistical differences in pre-operative (p=0.505) and post-operative (p<0.488) iHOT-12 scores when comparing the groups based on acetabular coverage. Mean iHOT-12 scores increased from 37.3 pre-operatively to 68.7 postoperatively, p<0.001, in the borderline dysplasia group, from 34.4 to 72, p<0.001, in the normal coverage group, and from 35.3 to 69.4, p<0.001, in the pincer group. These pre-operative scores increased by 31.4, 37.8, and 34.1, respectively, with no effect for acetabular coverage on the magnitude of change from pre-operative to post-operative iHOT-12 scores, F(2, 339) =1.18; p=0.310. 10 subjects (2.3%) underwent conversion arthroplasty and 19 patients (4.4%) underwent revision arthroscopy with no significant effect of acetabular coverage on the incidence of revision or conversion surgery, X2 (6, 433)=11.535, P = 0.073. Conclusion: Lateral acetabular coverage did not influence outcomes from primary hip arthroscopy performed in patients with low (borderline dysplasia), normal, and high (global pincer FAI) LCEA. Borderline dysplasia and moderate global pincer FAI with no or minimal osteoarthritis do not compromise successful 2-year minimum outcomes or survivorship following primary hip arthroscopy when performed by experienced surgeons.